2014
DOI: 10.1007/s13197-014-1359-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gamma irradiation on antioxidant properties of ber (Zizyphus mauritiana) fruit

Abstract: Effect of gamma irradiation (0.25 to 1.0kGy) on antioxidant properties of ber fruit was studied. Antioxidant properties of ber fruits were determined by Scavenging DPPH radical activity, reducing power assay, super oxide anion radical activity, TBARS, total phenolic content and total flavonoid content. Gamma irradiation treatment up to 1.0kGy elevated the Scavenging DPPH radical activity (9 %), super oxide anion radical activity (26 %) and total flavonoid content (208 %) compared to fresh ber fruit. On the oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 15 publications
(11 reference statements)
2
9
0
2
Order By: Relevance
“…A similar result was reported by Kavitha et al, 2015, who studied the effect of gamma irradiation (0.25 to 1.0 kGy) on antioxidant. The study revealed that irradiation treatment induced a significant enhancement in flavonoid content and superoxide anion radical activity and DPPH radical activity.…”
Section: Impacts Of Irradiation On Total Phenolic Content (Tpc)supporting
confidence: 86%
“…A similar result was reported by Kavitha et al, 2015, who studied the effect of gamma irradiation (0.25 to 1.0 kGy) on antioxidant. The study revealed that irradiation treatment induced a significant enhancement in flavonoid content and superoxide anion radical activity and DPPH radical activity.…”
Section: Impacts Of Irradiation On Total Phenolic Content (Tpc)supporting
confidence: 86%
“…Ber fruit powder has free radical (DPPH) capacity of 90.50% as shown in Table 1. These findings are in resemblance with Kavitha and Kuna (2014) who formulated ber RTS beverage. Likewise,ber juice vinegar was formed and due to its high antioxidant activity it was called as functional vinegar (Vithlani and Patel 2010).…”
Section: Instrumental Texture Parameterssupporting
confidence: 78%
“…Figure 3 showed that the pineapple flesh antioxidant system in terms of ascorbic acid and total phenolic content was not affected by gamma irradiation. Several reports confirm that enhanced antioxidant defense combats the oxidative stress induced by abiotic stressors such as UV radiation (Li et al, 2010;Kumari, Singh, & Agrawal, 2010) and gamma irradiation (Kavitha et al, 2015). An increase in phenolic compound biosynthesis and accumulation frequently occurs in plant tissues as a reaction to biotic and abiotic stresses (Dixon & Paiva, 1995).…”
Section: Discussionmentioning
confidence: 94%